Plano de ação para melhoria da atenção à saúde da gestante no pré-natal de alto risco no municipio de São Francisco do Conde - Ba - Pereira, Elane Souza De Oliveira (2023)
High-risk prenatal care plays a decisive role in the outcome of pregnancy, as it ensures the necessary care, identifies risk situations, allows timely interventions for the health of the pregnant woman and the fetus, and has a potential impact on reducing prematurity rates and neonatal and maternal morbidity and mortality. Such promotion reveals how it is necessary to expand care for pregnant women beyond the biological and physiological aspects and points to strategic actions for the work of the Social Service, in order to contribute to ensuring the improvement of access, coverage and quality of follow-up during the prenatal period. -natal care, delivery and postpartum care. Therefore, weaknesses were identified in the work of the high-risk prenatal team, such as the centralization of care and low recognition of Social Work as an essential profession in high-risk prenatal care. This work aims to elaborate an intervention project with the purpose of organizing high-risk prenatal care in Specialized Health Care in the city of São Francisco do Conde-BA, discussing the attributions and weaknesses with the team,planning and implementing actions to improve care practice and evaluate the intervention process in high-risk prenatal care. It is expected that this intervention project will be a powerful instrument of impact and transformation of the institutional and social reality, that it will contribute to the strengthening of the Unified Health System with a view to improving the maternal-infant indicator for the guarantee of the rights of pregnant women and the reaffirmation of the ethical-political project of Social Work. With this, it is intended that the health team reassess their practices in responding to the problems and health situations of highrisk pregnant women and promote adequate, welcoming care, with qualified listening and respectful treatment.